Clonal dynamics and Stereo-seq resolve origin and phenotypic plasticity of adenosquamous carcinoma - Ruiying Zhao; Yunhua Xu; Yedan Chen; Jiajun Zhang; Fei Teng; Sha Liao; Shengnan Chen; Qian Wu; Chan Xiang; Jiaohui Pang; Zhanxian Shang; Jikai Zhao; et al. (npj Precision Oncology, 2023)
Abstract The genomic origin and development of the biphasic lung adenosquamous carcinoma (ASC) remain inconclusive. Here, we derived potential evolutionary trajectory of ASC through whole-exome sequencing, Stereo-seq, and patient-derived xenografts. We showed that EGFR and MET activating mutations were the main drivers in ASCs. Phylogenetically, these drivers and passenger mutations found in both components were trunk clonal events, confirming monoclonal origination. Comparison of multiple lesions also revealed closer genomic distance between lymph node metastases and the ASC component with the same phenotype. However, as mutational signatures of EGFR-positive lung squamous carcinomas (LUSCs) were more comparable to EGFR-positive ASCs than to wild-type LUSCs, we postulated different origination of these LUSCs, with ASC being the potential intermediate state of driver-positive LUSCs. Spatial transcriptomic profiling inferred transformation from adenocarcinoma to squamous cell carcinoma, which was then histologically captured in vivo. Together, our results explained the development of ASC and provided insights into future clinical decisions.